2022
DOI: 10.1126/sciadv.adc9317
|View full text |Cite
|
Sign up to set email alerts
|

Brain lipidomics: From functional landscape to clinical significance

Abstract: Lipids are crucial components of cellular function owing to their role in membrane formation, intercellular signaling, energy storage, and homeostasis maintenance. In the brain, lipid dysregulations have been associated with the etiology and progression of neurodegeneration and other neurological pathologies. Hence, brain lipids are emerging as important potential targets for the early diagnosis and prognosis of neurological diseases. This review aims to highlight the significance and usefulness of lipidomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 150 publications
2
69
0
Order By: Relevance
“…To date, MALDI-IMS has not been employed to study ion profiles of ex vivo brain slices, in part due to the challenging requirement of handling the brain slices to extract them from their experimental setup and then section 400 μm thick brain slices down to just 10 μm without the use of an embedding material. Importantly, MALDI-IMS is uniquely equipped for lipid analysis with soft ionization and an untargeted mechanism, unlike targeted immunologic approaches. , Moreover, lipids are continuing to emerge as key players in neurologic disease and as important regulators of membrane-bound channels . Coregistration of electrophysiology and light transmittance imaging experiments in brain slices with MALDI-IMS would greatly increase our overall understanding of acute lipid changes in a variety of neuroscientific fields .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, MALDI-IMS has not been employed to study ion profiles of ex vivo brain slices, in part due to the challenging requirement of handling the brain slices to extract them from their experimental setup and then section 400 μm thick brain slices down to just 10 μm without the use of an embedding material. Importantly, MALDI-IMS is uniquely equipped for lipid analysis with soft ionization and an untargeted mechanism, unlike targeted immunologic approaches. , Moreover, lipids are continuing to emerge as key players in neurologic disease and as important regulators of membrane-bound channels . Coregistration of electrophysiology and light transmittance imaging experiments in brain slices with MALDI-IMS would greatly increase our overall understanding of acute lipid changes in a variety of neuroscientific fields .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, MALDI-IMS is uniquely equipped for lipid analysis with soft ionization and an untargeted mechanism, unlike targeted immunologic approaches. , Moreover, lipids are continuing to emerge as key players in neurologic disease and as important regulators of membrane-bound channels . Coregistration of electrophysiology and light transmittance imaging experiments in brain slices with MALDI-IMS would greatly increase our overall understanding of acute lipid changes in a variety of neuroscientific fields . To achieve this, we must first validate a technique for the preparation of ex vivo brain slices for MALDI-IMS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFA) are relevant for maintaining the neuronal structure and normal functioning of the brain. 13 They can be either consumed from food directly or synthesized by enzymatic desaturation, elongation and peroxisomal β-oxidation through nutritionally essential precursors α-linolenic acid (C18:3n-3, ALA) and linoleic acid (C18:2n-6, LA). 14 Since n-3 PUFA and n-6 PUFA compete for the same metabolic enzymes, it was reported that maintaining an optimally low n-6/n-3 PUFA ratio is linked to prevention of several diseases, such as depression.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, lipidomic analysis is becoming a valuable tool in biomedical research. It can be used to discover biomarkers for the early diagnosis and prognosis of many diseases and to understand their biological functions ( Yoon et al, 2022 ). As a result, understanding changes in lipid metabolism and their trafficking has mainly contributed to understanding the mechanisms behind various human diseases, including cancer, neurodegenerative diseases, diabetes, and obesity ( Adibhatla and Hatcher, 2008 ; Lu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%